Ultrasound‐Guided Percutaneous Needle Tenotomy for Chronic Tensor Fascia Lata Tendinopathy: A Case Series and Description of Sonographic Findings. Issue 9 (8th February 2018) - Bradberry, David M.; Sussman, Walter I.; Mautner, Kenneth R.
Abstract: Proximal tensor fascia lata tendinopathy at its origin on the anterior superior iliac crest is one potential cause of lateral hip pain. However, there is limited literature regarding the mechanism, disease course, or management of this condition. There is growing evidence supporting the effective treatment of percutaneous needle tenotomy (PNT) for chronic tendinopathy. Only a single case series has examined the efficacy of PNT for tendinopathy about the hip and pelvis. Presented here are examples of 2 cases of chronic recalcitrant proximal ultrasound confirmed tensor fascia lata (tendinopathy effectively treated with ultrasound‐guided PNT. Level of Evidence: IV